1995
DOI: 10.3354/dao022001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental transmission of green turtle fibropapillomatosis using cell-free tumor extracts

Abstract: Green turtle fibropapillomatosis (GTFP), characterized by multiple benign fibroepithelial tumors on the skin and eyes, has become a growing threat to green turtle Chelonja mydas populations worldwide. The cause of GTFP 1s unknown, but a viral etiology is suspected. This study investigated whether GTFP could be experimentally transmitted to young captive-reared green turtles using cell-free fibropapilloma extracts prepared from free-ranging turtles with spontaneous disease Turtles raised from eggs collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
0
5

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 17 publications
6
127
0
5
Order By: Relevance
“…Transmission studies have demonstrated that the infectious FP agent is less than 0.45 m in size and can be inactivated by organic solvents and high-speed centrifugation, which is consistent with the theory of an enveloped virus as the causative agent (36,37). Using PCR, FPTHV DNA has been found in most examined fibropapillomas but not detected in the vast majority of healthy turtles (45,47,54).…”
supporting
confidence: 50%
“…Transmission studies have demonstrated that the infectious FP agent is less than 0.45 m in size and can be inactivated by organic solvents and high-speed centrifugation, which is consistent with the theory of an enveloped virus as the causative agent (36,37). Using PCR, FPTHV DNA has been found in most examined fibropapillomas but not detected in the vast majority of healthy turtles (45,47,54).…”
supporting
confidence: 50%
“…Recent demonstration of tumor induction in healthy young turtles inoculated intradermally with cell-free homogenates of fibropapilloma strongly suggests a viral etiology for this slow-growing tumor (13). However, no infectious virus has been isolated in cell culture and the causative agent of GTFP has not been identified (11).…”
Section: Discussionmentioning
confidence: 99%
“…The disease, which disrupts the daily activities of affected animals, is characterized by the formation of lobulated fibrous tumors, frequently around the neck, eye, mouth, flipper and/or oral cavity, and occasionally within visceral organs, such as lung, kidney, and heart. Recent studies have implicated viruses, notably a herpesvirus and retrovirus, as the potential cause of green turtle fibropapilloma (GTFP) (1,6,13,25). However, to date, no virus has been isolated in cell culture, and the pathogenetic role of herpesviruses or retroviruses has not been established (11).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from controlled transmission experiments now implicates a filterable infectious agent, most probably a virus, as the primary cause of GTFP (8). Similar epithelial and fibro-epithelial tumors in other vertebrate species have also been shown to have viral etiologies (4,9).…”
Section: Etiology and Prevalence Of Gtfpmentioning
confidence: 99%